TAGLN2-Regulated Trophoblast Migration, Invasion and Fusion are Impaired in Preeclampsia - Wang, Hao; Zhang, Xiaowei; Liu, Chunfeng; Chen, Shengfu; Liu, Xinyang; Fan, Shangrong (Frontiers in Cell and Developmental Biology, 2022)
Preeclampsia (PE) is a serious disease during pregnancy that affects approximately 8 million mothers and infants worldwide each year and is closely related to abnormal trophoblast function. However, research on placental trophoblast functional abnormalities is insufficient, and the etiology of PE is unclear. Here, we report that the expression of transgelin-2 (TAGLN2) was downregulated in the placenta of patients with PE. In addition, a lack of TAGLN2 significantly reduced the ability of trophoblasts to migrate, invade and fuse. A co-immunoprecipitation (Co-IP) and microscale thermophoresis analysis showed that TAGLN2 bound directly to E-cadherin. A decrease in TAGLN2 expression led to a reduction in cleavage of the E-cadherin extracellular domain, thereby regulating the function of trophoblasts. In addition, we found that a reduction in soluble E-cadherin may also have an effect on blood vessel formation in the placenta, which is necessary for normal placental development. What’s more, the in vivo mouse model provided additional evidence of TAGLN2 involvement in the development of PE. By injecting pregnant mice with Ad-TAGLN2, we successfully generated a human PE-like syndrome that resulted in high blood pressure and some adverse pregnancy outcomes. Overall, the association between TAGLN2 and PE gives a new insight into PE diagnosis and treatment.